2019
DOI: 10.1016/j.ahj.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Validating the use of registries and claims data to support randomized trials: Rationale and design of the Extending Trial-Based Evaluations of Medical Therapies Using Novel Sources of Data (EXTEND) Study

Abstract: Background: Randomized controlled trials (RCTs) are the "gold standard" for comparing the safety and efficacy of therapies, but may be limited due to high costs, lack of feasibility, and difficulty enrolling "real-world" patient populations. The Extending Trial-Based Evaluations of Medical Therapies Using Novel Sources of Data (EXTEND) Study seeks to evaluate whether data collected within procedural registries and claims databases can reproduce trial results by substituting surrogate non-trial based variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…Trial cohort patients were linked to the CathPCI Registry from 2009 to 2011 using indirect identifiers and a deterministic algorithm based on the matching of age or date of birth, sex, PCI date, stent type, hospital discharge date, and a hospital identifier, as part of the broader EXTEND-DAPT Study (Extending Trial-Based Evaluations of Medical Therapies Using Novel Sources of Data). 12 The overall goal was to reweight the trial cohort to resemble the registry cohort regarding all measured covariates, and then to reestimate the randomized treatment effects in this reweighted sample (Figure 1). 10,11 To do so, we first pooled the linked trial cohort with the registry cohort and estimated models to predict the probability of trial participation for each individual based on sociodemographic information, medical history, cardiovascular history, presentation, and procedural characteristics captured in the CathPCI Registry using logistic regression.…”
Section: Methodsmentioning
confidence: 99%
“…Trial cohort patients were linked to the CathPCI Registry from 2009 to 2011 using indirect identifiers and a deterministic algorithm based on the matching of age or date of birth, sex, PCI date, stent type, hospital discharge date, and a hospital identifier, as part of the broader EXTEND-DAPT Study (Extending Trial-Based Evaluations of Medical Therapies Using Novel Sources of Data). 12 The overall goal was to reweight the trial cohort to resemble the registry cohort regarding all measured covariates, and then to reestimate the randomized treatment effects in this reweighted sample (Figure 1). 10,11 To do so, we first pooled the linked trial cohort with the registry cohort and estimated models to predict the probability of trial participation for each individual based on sociodemographic information, medical history, cardiovascular history, presentation, and procedural characteristics captured in the CathPCI Registry using logistic regression.…”
Section: Methodsmentioning
confidence: 99%
“…Details on this linkage have been published previously. 12 Data from patients included in the US CoreValve HiR (High Risk trial), SURTAVI (Surgical or Transcatheter Aortic‐Valve Replacement in Intermediate‐Risk Patients) trial, and single‐arm CAS (Continued Access Study) who could be successfully linked to US Centers for Medicare and Medicaid Services Medicare Provider Analysis and Review data set with procedure dates February 2, 2011, to September 30, 2015, were included. The CoreValve HiR randomized individuals at high surgical risk with severe aortic stenosis to undergo TAVR with the Medtronic CoreValve bioprosthesis versus SAVR.…”
Section: Methodsmentioning
confidence: 99%
“… 9 Moreover, in contrast to well‐defined and validated frailty metrics using in‐person measurements, physicians’ subjective assessments of frailty may not significantly predict risk in TAVR. 9 As such, retrospective ascertainment of frailty status, using claims algorithms developed on the basis of such validated metrics of frailty, has been advocated to improve risk prediction, 10 assessment of hospital care quality, 11 and evaluation of study generalizability 12 when frailty assessment using these validated techniques has not been performed. While we have previously demonstrated that a claims‐based frailty index (CFI) identifies individuals undergoing TAVR at higher risk of adverse outcomes than comorbidities alone using nationwide claims data, 10 whether it identifies individuals with a greater burden of frailty‐related health deficits and similarly identifies an increased risk of adverse outcomes in a clinical trial population remains uncertain.…”
Section: Figurementioning
confidence: 99%
“…Fifth, and finally, more data are needed for other cardiovascular devices and settings in which "real world" evidence could be used in the regulatory process. 10…”
Section: Next Stepsmentioning
confidence: 99%